Utilizing Silage-Based Bioconversion of Myctophid Biomass to Enhance Protein Content and Nutritional Value of Aquafeed: Myctophid Silage as an Aqua Feed Ingredient - Anas K. K.; Lekshmi R. G. Kumar; Tejpal C. S.; Fathima Rafni K. S.; Shamna N.; Anandan R.; N. P. Sahu; Suseela Mathew (Fishery Technology, 2024)
Myctophids, commonly known as lanternfish, play a pivotal role in the oceanic food web and are one of the most unexploited fishery resources. In this regard, the present study has been carried out to utilize myctophids as an aquafeed ingredient by subjecting them to an ensilaging process. Two myctophid fishes, N. microchir and D. watasei mixed in a 1:1 ratio (w/w) were subjected to formic acid mediated ensilaging. Biochemical changes were studied during the ensilaging process of 10 days, with sampling on every alternative day. The degree of hydrolysis (DH) increased throughout the ensilaging process, with the values ranging from 24.1% (0th day) to 59.45% (10th day). The increase in DH indicated the accelerated autolysis process by the formic acid addition. An increase in non- protein nitrogen content during the ensilaging process was found to be significant, and it indicates the hydrolysis of protein. Though the peroxide value has increased during the storage period, the values were within the acceptable range. Aquafeed prepared from the resultant silage by mixing with rice bran in a ratio of 2:1 (w/w) was found to have an increased protein content of 35.33%, suggesting that it can be a potential alternative for the protein source in fish feeds.